Effect of Blend of Silica Fume and Sisal Fiber on Performance of Concrete: Enhancing Concrete Performance through Silica Fume and Sisal Fiber Blend (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India is a developing country, therefore Infrastructure development is necessary for our country and concrete plays a vital role in it. Concrete is the world‘s largest consuming material in the construction field. The emission of carbon-dioxide (CO2) in the atmosphere from the operation and maintenance of structures as well as production of building materials can be reduced by using renewable resources and construction materials. Conventional concrete is relatively strong in compression but weak in tension, in order to overcome the weakness the use of a sufficient volume of certain fibers such as sisal fiber is used in this experiment, which is easily available, renewable and economical. Micro silica, an industrial byproduct which is a very fine non-crystalline material is very good as filler material to provide good strength. By utilizing these waste materials in construction activities which solve the environmental pollution problems, also safer and economical construction. The main objective of this project is to investigate effect of silica fume fiber orientation of sisal fiber on performance of concrete, which ultimately solve the problems of waste disposal reduces global warming. Here in the experiment an attempt has been made to increase the strength of concrete by replacing cement partially with silica fume and sisal fibers at varying percentage in a design mix of M30 and M40.